Roberto Andorno (h), La bioéthique et la dignité de la personne. Presses Universitaires de France. Paris 1997 (=Collection Médecine et Societé). 128 páginas - Massini Correas, Carlos I. (1998)
Fil: Massini Correas, Carlos I. Universidad de Mendoza; Argentina